2021
DOI: 10.3389/fmars.2021.807489
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Central Nervous System of Sea Slug (Onchidium reevesii) Exposed to Low-Frequency Noise

Abstract: Low-frequency noise has become a marine pollutant that cannot be ignored, but most studies have focused on the behavioral and physiological effects on marine vertebrates, with few studies in marine mollusks. Therefore, sea slug was used in this study to investigate the effect of low-frequency noise on its physiological aspects. This experiment was designed with different low-frequency noise (0, 100, 300, and 500 Hz) and different stimulation times (0, 6, and 12 h) to measure superoxide dismutase (SOD), malondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Cytokines are soluble extracellular proteins or glycoproteins that are key modulators of inflammation, participating in cells engaged in innate immunity via a complex and sometimes seemingly contradictory network of interactions (Turner et al, 2014). The latest study on Onchidium reevesii revealed that cytokine-cytokine receptor interaction pathway involved in resisting the low-frequency noise stress (Tu et al, 2021), andZhao et al (2016) analyzed the gene expression profiles of oyster gills that have found that cytokine-cytokine receptor interaction pathway was also involved in salinity tolerance. The lack of available oxygen contributes to a bioenergetic crisis within cells, which in turn can lead to cellular necrosis-promoting inflammatory processes in a non-specific manner through the release of intracellular contents into the surrounding space (Nizet and Johnson, 2009;Taylor and Colgan, 2017).…”
Section: Figure 7 |mentioning
confidence: 99%
“…Cytokines are soluble extracellular proteins or glycoproteins that are key modulators of inflammation, participating in cells engaged in innate immunity via a complex and sometimes seemingly contradictory network of interactions (Turner et al, 2014). The latest study on Onchidium reevesii revealed that cytokine-cytokine receptor interaction pathway involved in resisting the low-frequency noise stress (Tu et al, 2021), andZhao et al (2016) analyzed the gene expression profiles of oyster gills that have found that cytokine-cytokine receptor interaction pathway was also involved in salinity tolerance. The lack of available oxygen contributes to a bioenergetic crisis within cells, which in turn can lead to cellular necrosis-promoting inflammatory processes in a non-specific manner through the release of intracellular contents into the surrounding space (Nizet and Johnson, 2009;Taylor and Colgan, 2017).…”
Section: Figure 7 |mentioning
confidence: 99%